Dietary Intervention with Oatmeal in Patients with uncontrolled Type 2 Diabetes Mellitus – A Crossover Study - Delgado, Graciela; Kleber, Marcus E.; Krämer, Bernhard K; Morcos, Michael; Humpert, Per M.; Wiegand, Kerstin; Mauldin, Andy; Kusterer, Klaus; Enghöfer, Michael; März, Winfried; Segiet, Thomas; Lammert, Alexander (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background In a pilot study, we evaluated the efficacy of two days of oatmeal on insulin resistance and glucose metabolism and found a marked decrease of insulin requirements. The most important shortcoming of that study was that the interventions were not isocaloric (diabetes adapted diet: 1500 kcal/d vs. oatmeal 1100 kcal/d). To address these drawbacks we designed the OatMeal And Insulin Resistance (OMA-IR) study.Methods The study was a randomized, open label crossover dietary intervention study with consecutive inclusion of 15 patients with uncontrolled type 2 diabetes. The intervention comprised two days of oatmeal on days 3 and 4 of a 5 days hospital stay. During the control period, patients received a diabetes mellitus adapted diet only. The primary endpoint was the daily insulin requirement and glycemic control.Results Upon oatmeal treatment, the required insulin dose could be significantly reduced on the third and fourth day as compared to the second day of inpatient stay (82.0±30.3 and 69.9±29.9IU versus 112±36.2IU;P<0.001). During control treatment, insulin requirement did not change. There were no significant differences in the changes of mean blood glucose or fasting glucose between both treatments. HbA1c was lower four weeks after the oatmeal intervention.Conclusion In this crossover study, two days of oatmeal intervention allowed a highly significant reduction of required daily insulin doses while maintaining adequate metabolic control as compared to a diabetes adapted diet only. The beneficial effects of the intervention might last for several weeks as shown by the lower HbA1c four weeks after the intervention.
Keywords: insulin dose; fasting glucose; glycemic control